2021
DOI: 10.1002/brb3.2139
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen attenuates physical and psychological stress‐induced cognitive impairments in ovariectomized rats

Abstract: Introduction Women are more vulnerable to stress‐related disorders than men, which is counterintuitive as female sex hormones, especially estrogen, have been shown to be protective against stress disorders. Methods In this study, we investigated whether two different models of stress act differently on ovariectomized (OVX) rats and the impact of estrogen on physical or psychological stress‐induced impairments in cognitive‐behaviors. Adult female Wistar rats at 21–22 weeks of age were utilized for this investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…In adult women, E 2 may promote verbal memory and fluency ( Hamson, Roes & Galea, 2016 ). In gonadectomized male and female rats, E 2 was found to improve learning and memory even after physiological or psychological stressors ( Hamson, Roes & Galea, 2016 ; Khaleghi et al, 2021 ). Moreover, studies with castrated male rats suggested that learning may be improved by testosterone treatment ( Spritzer et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In adult women, E 2 may promote verbal memory and fluency ( Hamson, Roes & Galea, 2016 ). In gonadectomized male and female rats, E 2 was found to improve learning and memory even after physiological or psychological stressors ( Hamson, Roes & Galea, 2016 ; Khaleghi et al, 2021 ). Moreover, studies with castrated male rats suggested that learning may be improved by testosterone treatment ( Spritzer et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, menstruation, post-partum period, ovarian resection conditions, depression, and anxiety-like behavior are correlated with fluctuating levels of estrogen ( Pinkerton et al, 2010 ). A recent study reported acceleration in anxiety-like behavior in ovariectomized rats on their exposure to additional physical and psychological stressors, which was ameliorated with 17 β-estradiol treatment ( Khaleghi et al, 2021 ). Another study reported that one-year metformin therapy for ovariectomized rats ameliorated the long-term effects of ovariectomy-induced anxiety-like behavior ( Zakeri et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen-deficiency can induce spatial memory impairment, anxious, and depressive behaviors (Lagunas et al, 2010 ; Djiogue et al, 2018 ). Short-term estrogen treatment can address these physical and psychological stress-induced cognitive impairments (Khayum et al, 2020 ; Khaleghi et al, 2021 ), and prolonged regular (involuntary) exercise can improve estrogen levels in various brain regions and motor coordination performance (Rauf et al, 2015 ). Exercise also exerts the similar effects of estrogen in terms of lipid oxidation, fat reduction, and inflammation regulation in OVX mice (Jackson et al, 2011 ; Pighon et al, 2011 ; Gorres-Martens et al, 2018 ; Fuller et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%